Analysis of the energetic and productive effects derived by the installation of a conveyor belt in the metal-mechanic industry (2018)
Energy efficiency is a topic of interest due to the financial decisions that involve; high costs must be avoided and regulated by means of strategic decision with low-cost invest. The research presents an operational improvement in the production chain of metal parts in a metal-mechanic micro-enterprise by means of the installation of a conveyor belt, a comparison is made between the energy consumption of the previous system and the system with the conveyor belt, and the results present improvements in execution times, production and energy consumption per number of manufactured parts.